The development of a work-directed intervention on return to work for people living with colorectal cancer / Chow Sze Loon - Chow, Sze Loon (2016)
Traditionally, return to work (RTW) programmes have focused on enabling physically injured workers to resume duty at the workplace as part of the vocational rehabilitation process. Nevertheless, there is a lack of such RTW initiatives for individuals with chronic disease. A focus on RTW for colorectal cancer survivors is timely since colorectal cancer is the most common cancer among Malaysian men and affects the working age population. With earlier detection and better treatment regimes, survival rates are on the rise and cancer survivors are now living indefinite periods after diagnosis. However, there are few RTW studies for cancer, now considered a form of chronic disease. Therefore, this study aimed to develop a work-directed intervention on RTW for people living with colorectal cancer, using sequential mixed-method research methodology. This is a 3-phase mixed method cross sectional design consisting of a systematic review (Phase I), in-depth interview (Phase II) and feasibility study (Phase III). A RTW framework was developed following findings from a systematic review of 27 published studies on RTW. A criteria-based, purposive, maximum variation sampling method targeting colorectal cancer survivors, employers, and healthcare professionals was conceived and used a semi-structured topic guide for in-depth interviews. All themes discovered in Phase II on barriers and motivators in relation to RTW were grouped into different categories for analysis. The feasibility study of the proposed pathway for intervention in current practice (Phase III), was developed using a parallel mixed-method, by focusing on the modifiable factors identified in Phase I and Phase II. The feasibility component of this study was carried out using a Likert scale (Quantitative study) and in-depth interviews (Qualitative study) to gauge on the aspects of timing and flow of the intervention, contents of the intervention which included the materials used in it (educational leaflet, RTW brochure and fitness to work assessment form). Both quantitative and qualitative data contributed to the richness of data for iv analysis. Overall, RTW among cancer survivors is feasible but it depends on multiple factors. The importance of self-perceived work ability must be considered in the RTW intervention, besides the reported barriers and motivators. The RTW framework and findings from interviews revealed the potential areas for interventions by focusing on those identified modifiable factors. Key informants who participated in the feasibility study were younger, having many years remaining before retirement (colorectal cancer survivors), and appreciated the RTW process, being aware of the importance of work after illness and interested to learn more about RTW (healthcare professionals and employers in private sectors). The majority of the key informants agreed that the flow and timing of the RTW intervention were appropriate, tasks outlined in the RTW brochure emphasising early contact and constant communication with employers as well as the educational leaflet to be helpful in assisting timely RTW among colorectal cancer survivors. This intervention on RTW is feasible when the stakeholders are aware and carry out their respective tasks. Therefore, by reducing modifiable barriers and enhancing the motivators identified, the RTW outcome can be enhanced among colorectal cancer survivors.